The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/foods11142039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bergamot and Laoxianghuang Polysaccharides on Gut Microbiota Derived from Patients with Hyperlipidemia: An Integrative Analysis of Microbiome and Metabolome during In Vitro Fermentation

Abstract: The aim of this study was to investigate the effects of bergamot polysaccharide (BP) and Laoxianghuang polysaccharides (LPs, fermented bergamot) on the microbiome and metabolome during the in vitro fermentation of gut microbiota from patients with hyperlipidemia. Results indicated that both BP and LPs were able to increase the production of acetic acid, propionic acid, and butyric acid. However, only LPs could decrease the content of isobutyric acid and isovaleric acid, which are detrimental to gut health. A 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Lactobacillus johnsonii is a major microbiota in the BT group, perhaps this is a potential mechanism for the hypolipidemic efficacy of BT supplementation. An increasing number of research studies has suggested that a potential mechanism for dietary intervention to alleviate hyperlipidemia is the mediated production of short-chain fatty acids [55]. In the present study, hyperlipidemic mice supplemented with EFT were significantly enriched for Mucispirillum, a microorganism that typically produces short-chain fatty acids.…”
Section: Discussionmentioning
confidence: 78%
“…Lactobacillus johnsonii is a major microbiota in the BT group, perhaps this is a potential mechanism for the hypolipidemic efficacy of BT supplementation. An increasing number of research studies has suggested that a potential mechanism for dietary intervention to alleviate hyperlipidemia is the mediated production of short-chain fatty acids [55]. In the present study, hyperlipidemic mice supplemented with EFT were significantly enriched for Mucispirillum, a microorganism that typically produces short-chain fatty acids.…”
Section: Discussionmentioning
confidence: 78%
“…Micrographs recorded the appropriate magnification to obtain clear images at an acceleration voltage of 10.0 kV. The monosaccharide composition was determined according to our previous study [11].…”
Section: Structural Characterizationmentioning
confidence: 99%
“…The results of monosaccharide compositions analysis showed that BP was composed mainly of Mannose and Rhamnose, which was characterized as mannorhamnan. However, LPs mainly consisted of Galacturonic acid and Galactose, which were characterized as polygalacturonic acid (Figure S1) [11]. like layers of varying sizes (Figure 2B).…”
Section: Structural Characterizationmentioning
confidence: 99%
See 1 more Smart Citation